INGLIZ TILINI O‘QITISHDA AMALIYOTGA TATBIQ QILISHNING KOMPETENSIYAVIY YONDASHISH USULLARI - Jalilov, O.M. (SCIENCE and SOCIETY, 2023)
Exercises are important in the educational process, including language learning. Regardless of the type of lesson, the core part of any lesson plan is practice. Education is carried out through exercises that are divided into certain types and summarized in different classifications. A teacher may not be able to achieve his or her goals due to not using enough effective exercises or lack of effective exercises.
Keywords: semantic competence; intercultural competence; educational and cognitive competence; information competence